Can over-education account for the positive association between education and within-groups wage inequality? - Budría, Santiago (2015)
International evidence shows that conditional wage dispersion increases as we move towards more educated individuals. This paper asks whether over-education accounts for this fact. The answer is a resounding 'no'.